Dichotomy in Online Curriculum Development Approaches-Contemporary Online Learning Vis-a-Vis Computer Supported Collaborative Learning Environment - James Mathai, K. (Journal of Engineering Education Transformations, 2006)
The fields of learning theory, distance education theory and online curricular design in practice, are set for a paradigm change. The author in his research study while developing an exclusive 'Computer Supported Collaborative Learning (CSCL) Environment' based on 'Problem Based Learning (PBL)' curriculum design for adult learners has found dichotomy vis-a-vis 'Contemporary online learning environment' which is based on 'Subject structured' curriculum design approach. In this paper the author first justifies the need for PBL curricular design -as a paradigm change from the way present online learning environments are designed and developed for adult learners. The necessity of this change is to satisfy the Andragogical needs of adult learners and due to the dichotomy in the theoretical foundations (Objectivists' theory Vs. Constructivists' epistemology&Transactional Distance Theory), which has bearing on the development of an online learning environment. It follows with its implications on different aspects of curriculum development for an online learning environment. The aspects of curriculum considered are categorized as target learners, curriculum design models, Instructor 's role, communication design models, teaching/learning methodologies, goal orientation, pedagogical/andragogical philosophies, and development of learning skills and evaluation of learning. These aspects have been found to represent two extreme design views, when represented on a continuum. The implementation of which then lead to development of different types of learning environments. Today, most of the programmes offered in online learning mode to different target group of learners, are designed based on 'Behaviorist ' Pedagogical way of individualized learning. In this type of environment, the learner experiences courses as highly planned, structured for individual problem solving learning and reflection. To an adult learner such a learning environment does not satisfy andragogical needs. On the contrary, development of CSCL environment through an Internet based programme based on the emerging constructivists epistemology, transactional distance theory and implanted through PBL curriculum design will encourage andragogical way of learning. Finally in the above perspective, the paper elaborates and concludes the way instructional design and curriculum development for CSCL would be different to that of contemporary online learning environment.